Cerro Blanco 4.2 ka volcanic ash deposit at Cerro Colorado (Córdoba Province, Argentina) - Boretto, Gabriella Margherita (2023)
A tephra layer was recovered within the Holocene fluvial succession of the Cerro Colorado Cultural and Natural Reserve in the Córdoba Province (Argentina). Radiocarbon dating on organic matter preserved within the paleosoil beneath the tephra layer indicate that the ash layer is younger than ca. 4700 cal yr BP. Radiocarbon ages, Sr and Nd isotope data on the bulk rock, and microanalytical data on glass shards allow us to identify the Andean Central Volcanic Zone as the possible source area of the analyzed tephra. Our data highlight that the tephra layer recovered in the Córdoba Province was produced by volcanoes of the southern fringe of the Andean Central Volcanic Zone and that it can be confidently correlated with the Cerro Blanco 4200 cal yr BP eruption. These findings are also coherent with the known dispersion axis of the products of this eruption and allow further constraining their dispersion. This latter is extremely important for any attempt in volcanic hazard assessment.